TYPHLOPEDAGOGY: ITS SUBJECT, METHODS, AND DEVELOPMENT - Sulaymanova Muhlisa Kozimjon qizi; Umida Mexmanovna Utbasarova (Bright Mind Publishing, 2025)
This article analyzes the subject, main methods, historical development stages, and modern directions of the science of typhlopedagogy. It discusses the specific features of teaching and educating blind and visually impaired children, as well as pedagogical technologies that ensure their personal development. The article also explores the theoretical foundations and practical applications of typhlopedagogy.
Keywords: typhlopedagogy, blindness, visual impairment, special education, correctional pedagogy, sensory system, Braille alphabet, rehabilitation.